2011
DOI: 10.1111/j.1654-1103.2011.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of grassland species richness to local and landscape factors depend on spatial scale and habitat specialization

Abstract: Questions To what extent is species richness in semi‐natural grasslands related to local environmental factors and (present/past) surrounding landscape structure? Do responses of species richness depend on degree of habitat specialization (specialists vs generalists) and/or scale of the study? Location Öland, Sweden. Methods Richness of herbaceous vascular plants (subdivided into richness of grassland specialists and generalists) was recorded within 50 × 50 cm plots and 0.1–4.8 ha grassland polygons. Generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 49 publications
2
42
1
Order By: Relevance
“…The significant association between species composition in old grassland sites and the distribution of dispersal sources in the historical landscape may reflect a time lag in species' response to habitat fragmentation (e.g., Helm et al 2006). Plant species composition in grazed, previously arable (young) sites has also been shown to be dependent on the proximity to seminatural grasslands in the historical landscape (Cousins and Aggemyr 2008;Reitalu et al 2011), suggesting that grassland species have accumulated in the surrounding landscape over long periods of continuous grazing management.…”
Section: Discussionmentioning
confidence: 97%
“…The significant association between species composition in old grassland sites and the distribution of dispersal sources in the historical landscape may reflect a time lag in species' response to habitat fragmentation (e.g., Helm et al 2006). Plant species composition in grazed, previously arable (young) sites has also been shown to be dependent on the proximity to seminatural grasslands in the historical landscape (Cousins and Aggemyr 2008;Reitalu et al 2011), suggesting that grassland species have accumulated in the surrounding landscape over long periods of continuous grazing management.…”
Section: Discussionmentioning
confidence: 97%
“…4 Relationship between forest area and species richness of forest plant species in a small and b large plots (linear mixedeffects model, n.s. in both cases) and effect of length of forest edge on species richness of edge plant species in c small and d large plots with 95 % confidence bands (dashed lines) calculated from linear mixedeffects model Reitalu et al (2012) found a positive habitat area effect on species richness on a large plot scale (0.1-4.8 ha polygons), but there was no significant area effect on species richness at a small plot scale (0.25 m 2 ). This was true both for grassland specialist species and for generalist species.…”
Section: Discussionmentioning
confidence: 99%
“…The hills are isolated from other mountainous areas to the south-east (Shimba Hills), south (Usambara Mountains), south-west (Mt Kilimanjaro), west (Ngulia and Chyulu Hills) and north-west (Kenyan highlands) by the vast plains of Tsavo (Maeda et al, 2010). Annual rainfall is received during two major seasons (March-May, September -October) and varies between 480 -1200mm in the highlands (Reitalu et al, 2012), but much less rain (̴̴ ̴̴ 400mm) received on the surrounding plains of the lowlands (Pellikka et al, 2005).…”
Section: Study Sitementioning
confidence: 99%